The Tokyo Trial war criminals and Japan's postwar international relations - Higurashi, Yoshinobu 1962-
The Tokyo Trial, like the Nuremberg Trial, was unique as a judicial event. Presided over by eleven Allied judges, Japan's wartime leaders were individually tried in an international court of justice for crimes against international law. After two years of hearings, a majority judgment found twenty-five of the accused guilty; seven were sentenced to death. However, factionalism amongst justices and competing political interests served to undermine the final judgment, widely criticized as 'victor's justice.' Some seventy years later, its legacy continues to inform international politics and polarize ideological debate."--Page 4 of cover.